DOP066 Developing a core outcome set for fistulising perianal Crohn's disease. (16th January 2018) - Sahnan, K; Tozer, P J; Adegbola, S O; Lee, M J; Heywood, N; McNair, A G K; Hind, D; Yassin, N; Lobo, A J; Brown, S R; Sebastian, S; Phillips, R K; et al.
Abstract: Background: There is a need for improved therapies both medical and surgical for fistulising perianal Crohn's disease (pCD).However, lack of standardised outcome measures hamper effective analysis and comparison of data. The development of standardised outcome measures can resolve these issues and this study defines a core outcome set (COS) for fistulising pCD. Methods: A list of outcome measures was generated through a systematic review and patient-interviews. Outcomes measures were extracted verbatim and similar concepts categorised into domains ( n = 92) by three researchers and a patient representative. Consensus was established via online, three-phase Delphi process followed by a face-to-face meeting. Stakeholders were recruited nationally and were then grouped: panel one (Surgeons and Radiologists), panel two (Gastroenterologists and IBD nurses) and panel three (Patients). In phase one, participants were asked to score each outcome on a nine-point Likert scale based upon how important they felt it was in deciding whether the overall treatment of pCD had worked well. Outcomes that scored 7–9 by >70% of participants were included and de-novo outcomes added. In phase two, participants were shown graphical and numerical representations of their panel's scores and given the option to re-score based upon this information. In phase three, participants were shown graphical and numerical representations of all panels' scores and given the option to re-score based upon this information. No outcomes were excluded but the panel scores were used for the consensus meeting. The final COS was decided after consensus (>80% agreement) at the face-to-face meeting. Results: In total, 187/238 (78.5%) of the recruited participants completed round one (92 outcomes), 176/187 (94.1%) completed round two (80 outcomes, including five de-novo outcomes) and 183/187 (97.9%) completed round three (49 outcomes). The consensus meeting of 41 experts generated agreement on an eight domain COS. The COS comprised three patient-reported outcome, five clinician-reported outcome and an optional radiology domain. Conclusions: A fistulising pCD COS has been produced by all key stakeholders including patients. Application of the COS will reduce heterogeneity in outcome reporting, facilitating more meaningful comparisons between treatments, data synthesis and ultimately benefit patient care.